Disaster Planning: Important Papers and Documents - Josephine Turner (EDIS)
Disasters are a part of life. Whether the disaster is a hurricane, tornado or a terrorist attack preparation is the key to survival and to clean up after the event. Knowing where your family’s records and valuable documents are and being able to pick them up and take them with you, if you must evacuate, can save valuable time. For your “on the go” papers you will want to purchase a packet, folder, brief case or other carrying case for your documents. Place documents in this case in a secure but easily accessed location in your home. Then if you need to evacuate, important documents that need to go with you are in one place. This document is FCS9197, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: May 2003.